Synthesis and Spectral Analysis of Some Metal Ions Complexes with Mixed Ligands of Schiff Base and 1, 10-Phenanthroline - Baghdad Science Journal (مجلة بغداد للعلوم)
The free Schiff base ligand (HL1) is prepared by being mixed with the co-ligand 1, 10-phenanthroline (L2). The product then is reacted with metal ions: (Cr+3, Fe+3, Co+2, Ni+2, Cu+2 and Cd+2) to get new metal ion complexes. The ligand is prepared and its metal ion complexes are characterized by physic-chemical spectroscopic techniques such as: FT-IR, UV-Vis, spectra, mass spectrometer, molar conductivity, magnetic moment, metal content, chloride content and microanalysis (C.H.N) techniques. The results show the formation of the free Schiff base ligand (HL1). The fragments of the prepared free Schiff base ligand are identified by the mass spectrometer technique. All the analysis of ligand and its metal complexes are in good agreement with the theoretical values indicating the purity of Schiff base ligand and the metal complexes. From the above data, the molecular structures for all the metal complexes are proposed to be octahedral